The Impact Of Healthcare Providers On Effective Diabetes Management (The Review of Diabetic Studies, 2025)
BackgroundDiabetes mellitus represents a growing global health crisis, with rising prevalence of type 1 and type 2 forms driving morbidity from acute hypoglycemia and hyperglycemia across care settings. Nurses are pivotal in glycemic management, integrating monitoring, education, and coordination to mitigate these disturbances and their clinical burdens.​MethodsThis narrative review synthesized contemporary evidence from global epidemiological data, clinical guidelines, and studies on nursing interventions. Sources encompassed systematic reviews, randomized trials, and quality improvement reports detailing nurses' roles in assessment, insulin titration, patient education, and care models for hypo- and hyperglycemia prevention.​ResultsNurse-led interventions, including protocol-driven insulin adjustments, continuous glucose monitoring integration, and self-management education, improved HbA1c by 0.3-2.0%, reduced hypoglycemic events, and enhanced patient self-efficacy. Barriers like workload and knowledge gaps were offset by training and standardized protocols, yielding better outcomes in inpatient and community settings.​ConclusionsEmpowering nurses through education, protocols, and resources optimizes diabetes care, preventing glycemic extremes and supporting integrated management. Policy and practice should prioritize nursing competencies to address the escalating diabetes burden effectively.​